If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 6 + x = 4x Reorder the terms: 6 + X + x = 4x Solving 6 + X + x = 4x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + X + -6 + x = -6 + 4x Reorder the terms: 6 + -6 + X + x = -6 + 4x Combine like terms: 6 + -6 = 0 0 + X + x = -6 + 4x X + x = -6 + 4x Add '-1x' to each side of the equation. X + x + -1x = -6 + 4x + -1x Combine like terms: x + -1x = 0 X + 0 = -6 + 4x + -1x X = -6 + 4x + -1x Combine like terms: 4x + -1x = 3x X = -6 + 3x Simplifying X = -6 + 3x
| x(14+1)=3 | | 1.4x-7=0.06 | | AB+CB=DwhatsB | | x^3-2x^2-39x+72=0 | | 2x^3+15x^2+16x-12=0 | | 0.5(m-2)+0.6(m+3)=0.5(2m-4) | | (2x-6)(x+3)=2600 | | -3x+40=y | | 7=b+1 | | 12.890+0.12t=20 | | X+3x+2=q | | 33s+150=1000-150 | | 54677.23N=100000 | | 0.5(2x-3)-8=0.3(3x-4) | | abc=rfg | | 4x+2(x-6)=3x+5x+5 | | 14x+120-6x=200 | | 19x-8=9x-22 | | (10-3w)(w)=77 | | 8=1+x-5 | | 3x+2y+2z=3 | | 2v+13=-3(v-6) | | 2+f=9 | | 10-3w=2w-1 | | 38x+14=180 | | 8.50x-2.15x-3.15(5)=120 | | 3(3r-4)=-2(4-7r) | | -10+2x+40=x+4+2x | | 14=14s | | 9(-4x-5)=99 | | 36x+72=180 | | 182=13x+52 |